PENGARUH FUNGSI KEPEMIMPINAN, LINGKUNGAN KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA PERSONIL POLISI DI KANTOR KEPOLISIAN RESORT PASAMAN BARAT - Indra Syahputra; Yasri Hasim (Program Studi Magister Manajemen, 2015)
This study aimed to analyze the effect of leadership functions, work environment, and work motivation on personnel performance at the police station Pasaman Barat. Type of research is causative. The study population was all personnel at the police station Pasaman Barat. Sampling was based on stratified random sampling. Analysis of data used path analysis and hypothesis testing using the F test and t test. The results showed that: (1) The function of leadership a significant effect on work environment, (2) The function of leadership and work environment have a significant effect on work motivation, (3) The function of leadership, work environment, and work motivation have a significant effect on performance. (4) The function of leadership have a significant effect on performance through work environment, (5) The function of leadership have a significant effect on performance through motivation, and (6) work environment significant effect on performance through work motivation. This suggests that the function of leadership, work environment, and work motivation has a significant effect, directly or indirectly, to the performance of personnel at the police station Pasaman Barat. Keywords: leadership functions, work environment, work motivation, performance